Application of proteomics in fetal and neonatal medicine - Schanstra, Joost P. (Henry Stewart Talks, 2013)
Application of proteomics in fetal and neonatal medicine, Principles, Samples, Techniques, Statistics, Application to obstructive nephropathy in newborns, Application in neonatal medicine, Conclusion